An organelle-specific protein landscape identifies novel diseases and molecular mechanisms - Boldt, K; van Reeuwijk, J; Lu, Q; Koutroumpas, K; Nguyen, T-MT; Texier, Y; van Beersum, SEC; Horn, N; Willer, JR; Mans, DA; Dougherty, G; Lamers, IJC; et al. (Nature Publishing Group, 2016)
Cellular organelles provide opportunities to relate biological mechanisms to disease. Here we use affinity proteomics, genetics and cell biology to interrogate cilia: poorly understood organelles, where defects cause genetic diseases. Two hundred and seventeen tagged human ciliary proteins create a final landscape of 1,319 proteins, 4,905 interactions and 52 complexes. Reverse tagging, repetition of purifications and statistical analyses, produce a high-resolution network that reveals organelle-specific interactions and complexes not apparent in larger studies, and links vesicle transport, the cytoskeleton, signalling and ubiquitination to ciliary signalling and proteostasis. We observe sub-complexes in exocyst and intraflagellar transport complexes, which we validate biochemically, and by probing structurally predicted, disruptive, genetic variants from ciliary disease patients. The landscape suggests other genetic diseases could be ciliary including 3M syndrome. We show that 3M genes are involved in ciliogenesis, and that patient fibroblasts lack cilia. Overall, this organelle-specific targeting strategy sh ows considerable promise for Systems Medicine.